Mapping archaeal diversity in soda lakes by coupling 16S rRNA PCR-DGGE analysis with remote sensing and GIS technology - Elshafey, Naglaa (2022)
Fil: Elshafey, Naglaa. Al-Arish University. Faculty of Science. Botany and Microbiology Department; Egipto